2012
DOI: 10.3892/ijo.2012.1435
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the Nijmegen breakage syndrome 1 gene increases mammary tumor latency and metastasis

Abstract: Abstract. Human diseases such as Nijmegen breakage syndrome due to mutations in the NBS1 gene result in defects in resection of double strand breaks. NBS1 functions as part of the MRN complex which functions in homologous recombination and non-homologous end joining. NBS is a rare human autosomal recessive disorder caused by hypomorphic mutations. At the cellular level, NBS is characterized by radiosensitivity, chromosomal breakage and defective cell cycle checkpoints. NBS1 null mutations result in early embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition, it has recently been demonstrated that although NBS1 haploinsufficiency leads to increased mammary tumor latency in the MMTV-neu mouse model, the tumors that do form are characterized by high metastatic potential (240), further highlighting the role of NBS1 in tumor metastasis.…”
Section: Role Of Cell Cycle Checkpoint Control and Dna Repair Genes Imentioning
confidence: 99%
“…In addition, it has recently been demonstrated that although NBS1 haploinsufficiency leads to increased mammary tumor latency in the MMTV-neu mouse model, the tumors that do form are characterized by high metastatic potential (240), further highlighting the role of NBS1 in tumor metastasis.…”
Section: Role Of Cell Cycle Checkpoint Control and Dna Repair Genes Imentioning
confidence: 99%
“…Clearly nibrin is required for radiation induced apoptosis and the p70-nibrin product of the hypomorphic c.657 661del5 mutation is sufficient to uphold this function. Indeed, even enhanced apoptosis has been previously reported in irradiated NBS patient cells [33] and in a haploinsufficient mouse model [34]. Furthermore, the early embryonic lethality of Nbn null mutants was due to massive apoptosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Examining mice heterozygous for a null mutation, Nbn ins6 , indicated an increased tumour occurrence without loss of the remaining wild type allele [8]. Similarly, the same Nbn ins6 mutation on a mammary tumour prone MMTV-neu background lead to the development of highly metastatic mammary tumours [34]. We have examined here the mutation frequency in mice heterozygous for a null mutation in Nbn and although we find no evidence for an increased basal mutation rate, we do see a shift in mutation spectrum in comparison to wild type mice.…”
Section: Discussionmentioning
confidence: 99%